Molecular and ampelographic characterisation of Vitis vinifera L. "Albariño", "Savanin Blanc" and "Caino Blanco" shows that they are different cultivars - Santiago, J.L.=700 1 Boso, S.; Gago, P.; Alonso Villaverde, V.; Martinez, M.C.
(En, Es)
Ilus., 41 ref.
Keywords: VITIS VINIFERA; IDENTIFICACION; MICROSATELITES; VARIEDADES; ESPAÑA